Expression of pro-apoptotic and anti-apoptotic proteins in granulosa cells of women with diminished ovarian reserve - Bulgurcuoğlu Kuran, Sibel; Altun, Ayşe; Karamustafaoğlu Balcı, Burçin; Keskin, İlknur; Hocaoğlu, Meryem (Springer, 2022)
Purpose To evaluate the expressions of caspase-3 and cytochrome c and heat shock protein 70 (Hsp70) in granulosa cells (GCs) from women with normal ovarian reserve (NOR) and diminished ovarian reserve (DOR) undergoing intracytoplasmic sperm injection (ICSI). Methods GCs were collected from 117 infertile women during oocyte retrieval. Patients were classified into four groups as follows: DOR-COC score of 0, DOR-COC score of I, NOR-COC score of 0, and NOR-COC score of I. The caspase-3, cytochrome c, and Hsp70 analyses were performed immunohistochemically in GCs. The ICSI outcomes were evaluated prospectively. Results The clinical pregnancy and live birth rates were higher in DOR-COC score of I (15, 30.6%; 14, 38.9%) and NOR-COC score of I (19, 38.77%; 19, 52.7%) groups, compared with DOR-COC score of 0 (12, 24.4%; 3, 6.1%) and NOR-COC score of 0 (3, 6.1%; 0%) groups (p = 0.0001; 0.00002), respectively. Caspase-3 and cytochrome c expression levels were higher in DOR-COC score of 0 (23, 65.7%; 25, 71.4%) and NOR-COC score of 0 groups (19, 61.3%; 20, 64.5%), compared with DOR-COC score of I (8, 32%; 9, 36%) and NOR-COC score of I groups (7, 26.9%; 8, 30.8%) (p = 0.00297; p = 0.002), respectively. Lower expression levels of Hsp70 were found in DOR-COC score of 0 (11, 31.4%) and NOR-COC score of 0 groups (10, 32.3%), compared with DOR-COC score of I (16, 64%) and NOR-COC score of I groups (20, 76.9%) (p = 0.001), respectively. Hsp70 expression levels were positively correlated with the number of day 3 good-quality embryo and negatively correlated with estradiol levels in the DOR group. Conclusion Our data suggest that COC score of 0 is associated with increased expression levels of apoptotic proteins, decreased expression levels of anti-apoptotic protein, and poor ICSI clinical outcomes in women with and without DOR.
Keywords: Apoptosis; Caspase-3; Cumulus–Oocyte Complex; Cytochrome C; Diminished Ovarian Reserve; Heat Shock Protein 70; In Vitro Fertilization